2021
DOI: 10.3389/fimmu.2021.758154
|View full text |Cite
|
Sign up to set email alerts
|

Normal T and B Cell Responses Against SARS-CoV-2 in a Family With a Non-Functional Vitamin D Receptor: A Case Report

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has severely impacted daily life all over the world. Any measures to slow down the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and to decrease disease severity are highly requested. Recent studies have reported inverse correlations between plasma levels of vitamin D and susceptibility to SARS-CoV-2 infection and COVID-19 severity. Therefore, it has been proposed to supplement the general population with vitamin D to reduce the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Importantly, it was found that vitamin D is required for IFNg-mediated enhancement of cathelicidin. This is in agreement with studies showing that vitamin D deficiency is associated with impaired expression of cathelicidin and increased susceptibility to some infectious diseases, including TB (8)(9)(10)(11)(12)(13)(14)(15). This could also be an important mechanism explaining the beneficial role of vitamin D in TB prevention and treatment (16,17).…”
Section: Introductionsupporting
confidence: 91%
“…Importantly, it was found that vitamin D is required for IFNg-mediated enhancement of cathelicidin. This is in agreement with studies showing that vitamin D deficiency is associated with impaired expression of cathelicidin and increased susceptibility to some infectious diseases, including TB (8)(9)(10)(11)(12)(13)(14)(15). This could also be an important mechanism explaining the beneficial role of vitamin D in TB prevention and treatment (16,17).…”
Section: Introductionsupporting
confidence: 91%
“…33,44 In contrast, other CD4 + T cell subsets such as T H 2 and T H 17 do not seem to play a protective role for SARS-CoV-2 infections. 33,44 These findings are consistent with a classical function of T H 1 cells in antiviral immune responses, as T H 1 cells generally have direct antiviral functions, recruit monocytes to infected tissues and/or help activation and expansion of antiviral CD8 + T cells. Indeed, SARS-CoV-2-specific CD8 + T cells are also detected in the majority of COVID-19 convalescent individuals.…”
Section: Immunity To Sars-cov-2 Infectionsmentioning
confidence: 99%
“…To resolve the controversy outlined above, we and others have investigated the impact of VDR signalling on the immune response against SARS-CoV-2. 44,90 We have recently identified and described a female patient suffering from hereditary vitamin D resistant rickets (HVDRR) (OMIM: 277440). HVDRR is an autosomal recessive disorder where mutations in the VDR render the receptor dysfunctional.…”
Section: Molecular Studies Of Vitamin D In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Interestingly, a recent paper by Kongsbak-Wismann et al showed a normal T cell and B cell response during a SARS-CoV-2 infection in one homozygous and two heterozygous patients for mutations in VDR. These mutations totally abolish transcriptional activity after the vitamin D binds the receptor [ 37 ]. In the above-mentioned patients, the specific T cell response characterized by IFN gamma, IL-2, and TNF secretion as well as B cell response characterized by anti-RBD IgG antibodies were preserved [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations totally abolish transcriptional activity after the vitamin D binds the receptor [ 37 ]. In the above-mentioned patients, the specific T cell response characterized by IFN gamma, IL-2, and TNF secretion as well as B cell response characterized by anti-RBD IgG antibodies were preserved [ 37 ]. This demonstrates that an efficient immune response during SARS-CoV-2 infection does not require vitamin D signaling; however, vitamin D may influence the course of the disease by modulating other antiviral mechanisms, such as antibacterial peptides [ 14 ].…”
Section: Discussionmentioning
confidence: 99%